Regional features of agriculture development of the Republic of Sakha (Yakutia) - Fedorova Ekaterina; Fedorova Paraskovya (E3S Web of Conferences, 2020)
The article reveals development peculiarities of agriculture in the Republic of Sakha (Yakutia). The most important factor determining the social and economic development of Yakutia including agricultural sectors is its location in the Far North. In this regard, the main problems of regional agro-food complex development are studied, being the conduct of agricultural production in harsh natural and climatic conditions, seasonal nature of production, weak logistics and transport infrastructure, the complexity of agricultural producers to markets. The volume of gross regional product production per capita was analyzed. The main indicators of republican agriculture, as well as indicators of self-sufficiency level of basic agricultural products in Yakutia were considered. As a result of the study, the main specific features of agriculture development of the studied region were revealed.